Green logistics practices among logistics service provider in Malaysia - Kanisen, Jivarajah; Sabar, Rohafiz (2012)
The purpose of this paper is to find the measures and steps taken by the logistics service provider in Malaysia on applying green logistics in their daily operations to reduce the negative externalities on environment,Green logistics is concerned with producing and distributing goods in a sustainable way, taking account of environmental and social factors.It also refers to a sustainable logistics which suggests compatibility with the environment.Green logistics can have major impact on reducing the environmental burden of the industry especially in terms of greenhouse gases emissions and pollutions.